Nothing about us without us : disability oppression and empowerment - Charlton, James I. (Berkeley : University of California Press, 1998)
James Charlton has produced a ringing indictment of disability oppression, which, he says, is rooted in degradation, dependency, and powerlessness and is experienced in some form by five hundred million persons throughout the world who have physical, sensory, cognitive, or developmental disabilities. Nothing About Us Without Us is the first book in the literature on disability to provide a theoretical overview of disability oppression that shows its similarities to, and differences from, racism, sexism, and colonialism. Charlton's analysis is illuminated by interviews he conducted over a ten-y.
COVER; TITLE; COPYRIGHT; CONTENTS; THE ARGUMENT; ACKNOWLEDGMENTS; PEOPLE INTERVIEWED; PART I. INTRODUCTION; 1. Nothing About Us Without Us; PART II. DISABILITY OPPRESSION AND EVERYDAY LIFE; 2. The Dimensions of Disability Oppression: An Overview; 3. Political Economy and the World System; 4. Culture(s) and Belief Systems; 5. Consciousness and Alienation; 6. Observations on Everyday Life; PART III. EMPOWERMENT AND ORGANIZATION; 7. Empowered Consciousness and the Philosophy of Empowerment; 8. The Organization of Empowerment; PART IV. CONCLUSION; 9. The Dialectics of Oppression and Empowerment.
Includes bibliographical references (pages 179-194) and index.
Print version record.
eBooks on EBSCOhost
Keywords: People with disabilities -- Civil rights; People with disabilities -- Social conditions; Discrimination against people with disabilities; Sociology of disability; Stigma (Social psychology); People with disabilities; Human rights; Control (Psychology); Prejudices; Disabled Persons; Human Rights; Power, Psychological; Prejudice; Stereotyping; Personnes handicapées -- Droits; Personnes handicapées -- Conditions sociales; Discrimination à l'égard des personnes handicapées.; Handicap -- Aspect sociologique; Stigmatisation (Psychologie sociale); Personnes handicapées.; Droits de l'homme (Droit international); Contrôle (Psychologie); Préjugés.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; MEDICAL -- Health Care Delivery; Prejudices; People with disabilities; Human rights; Control (Psychology); Discrimination against people with disabilities; People with disabilities -- Civil rights; People with disabilities -- Social conditions; Sociology of disability; Stigma (Social psychology); Behinderung; Bürgerrechtsbewegung; Stigmatisierung; Gehandicapten; Discriminatie (sociologie); Stigmatisering (sociale wetenschappen); Politieke aspecten